Nanoparticles for controlled delivery and sustained release of chlorhexidine in the oral environment. (6th April 2015) - Garner, S; Barbour, ME
<x xml:space="preserve">Abstract</x> Objectives Chlorhexidine (CHX) is in widespread use as a topical antimicrobial agent. Within the field of oral medicine, it is used in the prevention of ventilator‐associated pneumonia as well as in the treatment of oral candidosis and microbial‐associated lichenoid reactions. The objective of this study was to develop a strategy for controlled, sustained topical delivery of CHX using nanoparticle technology. Methods Chlorhexidine was applied to hydroxyapatite, selected as a tooth analogue, as conventional CHX digluconate solutions and as aqueous suspensions of CHX hexametaphosphate nanoparticles with total CHX concentrations of 1, 2.2 and 5 mM. Soluble CHX release from the treated hydroxyapatite was monitored over a period of 7 days. Results A repeated‐measures ANOVA with post hoc LSD test indicated that CHX release was 2–3× greater, and sustained for longer, when CHX was delivered as CHX hexametaphosphate nanoparticles than in aqueous solution with 2.2 and 5 mM CHX (P = 0.020 and 0.013, respectively), but there was no statistically significant difference at 1 mM CHX (P = 0.172). Conclusions Chlorhexidine hexametaphosphate nanoparticles increased both the local dose and duration of soluble CHX delivery when applied to hydroxyapatite surfaces. This may provide a means to deliver a sustained dose of CHX with less frequent interventions.